Byzantine Military Tactics in Syria and Mesopotamia in the 10th Century - Theotokis, Georgios.
1 online resource (361 pages)
Keywords: This book examines the strategies and military tactics of the Byzantines and their enemies in Eastern Anatolia, Syria and in Upper Mesopotamia in the tenth century.